Benthic communities under anthropogenic pressure show resilience across the Quaternary. Issue 9 (20th September 2017) - Martinelli, Julieta C.; Soto, Luis P.; González, Jorge; Rivadeneira, Marcelo M.
Abstract : The Southeast Pacific is characterized by rich upwelling systems that have sustained and been impacted by human groups for at least 12 ka. Recent fishing and aquaculture practices have put a strain on productive coastal ecosystems from Tongoy Bay, in north-central Chile. We use a temporal baseline to determine whether potential changes to community structure and composition over time are due to anthropogenic factors, natural climatic variations or both. We compiled a database ( n  = 33 194) with mollusc species abundances from the Mid-Pleistocene, Late Pleistocene, Holocene, dead shell assemblages and live-sampled communities. Species richness was not significantly different, neither were diversity and evenness indices nor rank abundance distributions. There is, however, an increase in relative abundance for the cultured scallop Argopecten, while the previously dominant clam Mulinia is locally very rare. Results suggest that impacts from both natural and anthropogenic stressors need to be better understood if benthic resources are to be preserved. These findings provide the first Pleistocene temporal baseline for the south Pacific that shows that this highly productive system has had the ability to recover from past alterations, suggesting that if monitoring and management practices continue to be implemented, moderately exploited communities from today have hopes for recovery.